THE EFFECTS OF ENERGY DRINKS ON DENTAL HARD TISSUES: A CHEMICAL, MORPHOLOGICAL AND CLINICAL ANALYSIS - Maxmudjon Madumarov Ma‘rufovich (Research Focus International Scientific Journal, 2026)
Energy drinks have rapidly gained global popularity, yet their physicochemical properties raise concerns regarding dental health, particularly the integrity of hard dental tissues. These beverages typically contain high concentrations of organic acids (e.g., citric acid), sugars, and other additives that produce a low pH environment in the oral cavity, below the critical threshold (pH 5.5) for enamel demineralization. This review synthesizes the current scientific understanding of how energy drinks interact with enamel and dentin at chemical, morphological, and clinical levels. Chemical acidity promotes dissolution of hydroxyapatite, while titratable acidity and acid composition amplify demineralization beyond the effects of pH alone. Morphological analyses using microscopy techniques show increased surface roughness and loss of structural integrity after exposure. Although clinical evidence varies, in‑vitro and epidemiological data consistently demonstrate the erosive potential of energy drinks on dental hard tissues. Comprehensive preventive strategies focusing on reducing exposure and enhancing remineralization are essential to mitigate these adverse effects.